The “Great Meme War:” the Alt-Right and its Multifarious Enemies - Maxime Dafaure (Angles)
In this essay, I discuss how the alt-right has brought back into fashion traditional tenets of the reactionary, xenophobic, and often racist far-right, as demonstrated by George Hawley, and how it has managed to make these tenets appear as novel, provocative, and updated to the 21st century U.S. society and digital environment. I argue that to do so, alt-righters relied heavily on the creation, and sometimes reappropriation, of enemy images, with the ultimate goals of provoking outrage, instilling fear and/or hatred towards specific groups, reinforcing a sense of belonging within their own community, or more broadly manipulating collective perceptions and representations, first online then in real life. Indeed, the election of Donald Trump was hailed by the online alt-right as one of their major successes. With the help of irony, subversion, and often carefully engineered propaganda-like messages and images, the alt-right, it boasts, “meme’d into office” the Republican candidate. This paper consequently leads to an analysis of real-life repercussions of such adversarial rhetoric, notably through examples of recent far-right domestic terrorism in the US, and to a reflection on their place in an age of post-truth, fake news, and alternative facts. This contribution focuses on several enemy images. The first is that of the civilizational enemy from the outside, which uses the traditional process of othering. This theme is linked to Trump’s campaign and to his attacks against two major “enemies” of the U.S., namely Hispanics and Muslims. With the alt-right, refugees for example become “rapefugees,” which easily appeals to rampant islamophobia. The second enemy image created by the alt-right consists in its ideological opponents. Here, the function of the enemy image is to discredit opponents and their views (“cuckservative,” “feminazi,” or the sarcastic “Social Justice Warrior”). The third enemy image establishes a link between the first two. It depicts what I would call the “enemy within,” a common thread (or threat) in far-right ideologies. Indeed, cultural Marxism, a widespread conspiracy theory among the alt-right, is what its proponents believe to be the hidden reason for the perceived decline of the Western civilization. According to this worldview, the ideological opponents push a conspiracy against the West and its values. The recurring claims of a liberal bias among the media and academia also belong to this conspiracy theory. It also embraces elements of anti-Semitism, as well as traditional aspects of anti-communism, reminiscent of the historical Red Scares. Such a theory thus provides its believers with a broader narrative, as well as with a common enemy to rally against, and therefore builds a form of intersectionality among various online fringe groups.